Kinetic and Thermodynamic Studies in Cellulose Acetate-Polybutylene Succinate(CA-PBS)/Single Solvent/Water System for Desalination Membrane - Retno Dwi Nyamiati; Siti Nurkhamidah; Yeni Rahmawati; Wahyu Meka (Eksergi, 2023)
The most important part of the membrane synthesis process so that it has the desired pores is the solidification process of the membrane, the process begins with a change from one liquid phase into two liquid phases (liquid-liquid demixing). At a certain period during demixing, the polymer-rich phase solidifies; thus, a dense membrane matrix is formed. Parameters that determine the mechanism of membrane formation are based on thermodynamics including phase separation of Solvent-Polymer-Non-solvent which is explained through a phase diagram (Flory-Huggins Theory). This study aims to determine the initial prediction of the formation of CA-PBS membranes with various solvents used and variations of non-solvents in the best system, which is proven by its characteristics and performance when applied to desalination membranes which include ternary diagrams using cloud point data, solubility parameters with Hansesn solubility, the solvent-non-solvent diffusivity using the Tyn Calus Equation approach and the morphological proofing of the membrane through SEM photos, and the performance of the resulting membrane through salt rejection and permeate flux. The results of the difference in solubility parameters are can be predicted that using DMF solvent on the CA-PBS membrane can reduce the pore size and eliminate voids and macrovoids in the membrane morphology.